Structural basis for anticancer drug design : g-quadruplex-ligand complexes and aptamers - Chung, Wan Jun (2015)
Guanine-rich oligonucleotides have the propensity to fold into four-stranded helical structures known as G-quadruplex (G4). These structures are involved in cellular processes including replication, transcription and translation, with recent studies demonstrating their existence in cells. G4-forming genomic sequences were shown to be viable drug targets, while synthetic G4 aptamers were demonstrated to elicit anticancer activity. Hence, structural insights on G4-ligand complexes and G4 aptamers will be invaluable for G4-based drug design and development. This thesis is focused on two parts: I) structural study of two complexes between G4s and two highly efficient G4- binders, a telomestatin derivative and a bisquinolinium compound, and II) structural characterization of a G4 isolated from an anticancer aptamer, using NMR spectroscopy and X-ray crystallography. Strikingly, this G4 exhibits an unprecedented left-handed twist, which could serve as a unique recognition element.